Waiting for Godot : - Beckett, Samuel (Grove Press, 1954)
Waiting for Godot, written directly in French in 1948, has its world premiere on January 5, 1953, in Paris. The classic of modern theatre and perennial favorite of colleges and high schools. "One of the most noble and moving plays of our generation . . . suffused with tenderness for the whole human perplexity . . . like a sharp stab of beauty and pain."--The London Times.